Duodenal adenocarcinoma in a 10-year-old boy - Zouari Mohamed; Bouthour Habib; Ben Abdallah Rabia; Hlel Youssef; Ben Malek Riath; Gharbi Youssef; Kaabar Nejib (African Journal of Paediatric Surgery, 2014)
Gastrointestinal malignancies are extremely rare in the paediatric population and duodenal cancers represent an even more unusual entity. It represents 0.3-1% of all gastrointestinal tumours. A case report of a 10-year-old boy with duodenal adenocarcinoma is reported and the difficulties of diagnosing and treating this rare tumour are discussed.